Victor Papanek : the politics of design - Kries, Mateo, 1974-; Klein, Amelie; Clarke, Alison J. (Vitra Design Museum ; Victor J. Papanek Foundation, 2018)
The designer, author, and design activist Victor J. Papanek anticipated an understanding of design as a tool for political change and social good that is more relevant today than ever. He was one of the first designers in the mainstream arena to critically question design's social and ecological consequences, introducing a new set of ethical questions into the design field. This book presents an encompassing overview of Papanek's oeuvre, at the heart of which stood his preoccupation with the socially marginalized and his commitment to the interests of areas then called the Third World, as well as his involvement in the fields of ecology, bionics, sustainability, and anti-consumerism.
Keywords: 20. století; design; designéři; designers; sborníky; papers of several authors